Sex and the city: branding, gender and the commodification of sex consumption in contemporary retailing - Martin, Amber; Crewe, Louise (SAGE Publications, 2016)
This paper explores the changing spatiality of the sex retail industry in England and Wales, from highly regulated male orientated sex shops, pushed to the legislative margins of the city and social respectability, towards the emergence of unregulated female orientated ‘erotic boutiques’ located visibly in city centres. This is achieved through an exploration of the oppositional binaries of perceptions of sex shops as dark, dirty, male orientated, and ‘seedy’ and erotic boutiques as light, female orientated and stylish, showing how such discourses are embedded in the physical space, design and marketing of the stores and the products sold within them. More specifically, the paper analyses how female orientated sex stores utilise light, colour and design to create an ‘upscaling’ of sexual consumerism and reflects on what the emergence of up-scale female spaces for sexual consumption in the central city might mean in terms of theorisations of the intersectionality between agency, power, gender and class. The paper thus considers how the shifting packaging and presentation of sex-product consumption in the contemporary city alters both its acceptability and visibility.